The Influence of Parents’ Motivation on Anxiety in Tooth Extraction of Students At Elementary School Maryam Surabaya - Alya Nissah Yudianita; Ratih Larasati; Agus Marjianto; Sri Hidayati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Anxiety regarding teeth extraction among Maryam Surabaya Elementary School students is still quite high, at 80%, according to the collection of data. Parental motivation is one of several elements that might lessen student worry. As a result, the purpose of this study was to examine the influence of parental motivation on anxiety in tooth extraction among Maryam Surabaya Elementary School pupils. This study included cross-sectional analytic methodologies, including simple random sampling and purposive sampling. The research sample consisted of 76 Maryam Surabaya Elementary School students who had got tooth extraction therapy in health services. This study was carried out at Maryam Surabaya Elementary School in January 2023. The spearman rank correlation test was used in data processing and analysis procedures. The study's findings were based on the spearman rank correlation test, which yielded results for parental motivation (mean ± SD 37.95 ± 5.08) and student anxiety (mean ± SD 20.87 ± 10.20). ρ (0.032) < 0.05 was achieved, indicating that H0 is rejected. As a result, it can be inferred that parental motivation has an influence on anxiety in tooth extraction of Maryam Surabaya Elementary School students.